A Qualitative Research Study to Explore Perspectives From Individuals Involved in the ROCKET (Reading for Older People, Connecting With Kids and Enjoying Time Together) Intergenerational Reading Project - Rachel Rice; Ursula Shepherd; Lindsey Cameron; Lisa Dikomitis; Joanne Rodda (BJPsych Open)
Aims: Intergenerational programmes provide meaningful social contact for older people, and address negative stereotypes of ageing in children. Reading aloud improves language acquisition and literacy in children, however in regions of socio-economic deprivation, many children lack this opportunity. The aim of this qualitative research was to explore the experiences and perspectives of teachers and volunteers involved in an intergenerational reading project within a primary school in an area of high socioeconomic deprivation.